Obnova gozda po gradaciji velikega smrekovega lubadarja (Ips typhographus) v drugotnih smrekovih gozdovih na Kočevskem - Krese, Anže (Gozdarski vestnik, 2015)
In 2003 within the management unit Vrbovec (Kočevje) a massive bark beetle (Ips typhographus) outbreak occurred in the secondary Norway spruce forest. In order to determine the current status and ten-year development of regeneration and to identify the main factors influencing regeneration, 240 research plots (1.5 m x 1.5 m) were inventoried in 2005 and 2013. The plots were equally distributed with regard to the following factors: fencing, position within opening (centre / edge) and relief (plateau / sink-hole). Seedlings were monitored according to the species, age and height classes on these plots. The herb layer was also investigated. In 2005 and 2013 the total seedling density amounted to 58.000 and 43.000 specimens / ha. At the first inventory, tree species mixture was dominated by Norway spruce (77%), followed by pioneer species (12%). With the development of the regeneration the proportion of spruce decreased to 65%, while the increase of the pioneers (20%) was the most notable. The impact of overbrowsing was also observed. Fenced openings were characterised by a greater overall density of regeneration, more favourable seedling height structure, and 3.5 times higher coverage of broadleaves. Seedling density of individual tree species was influenced by the distance to seed trees (lime) and the distance to the edge of openings (spruce). Development of regeneration indicated gradual improvement of the microclimate conditions in the future. The seed potential and the appropriate forest tending may favour development of the climax tree species (beech) in the future.
Keywords: naravno pomlajevanje; gradacija; veliki smrekov lubadar; ograje; Picea abies (L.) Karst.